Childhood happiness and violence: a retrospective study of their impacts on adult well-being. Issue 9 (20th September 2013) - Bellis, Mark A; Hughes, Karen; Jones, Alyson; Perkins, Clare; McHale, Philip
Abstract : Objectives: To examine the hypothesis that adult well-being is related to childhood experiences independent of current adult sociodemographic conditions. Design: A cross-sectional, stratified, randomised sample survey using self-assessed measures of current well-being and retrospective measures of childhood experiences. Setting: Households in North West England (September 2012–March 2013). Participants: The individual with the next birthday in randomly selected households (n=11 500; compliance 89.6% of eligible households). Analysis was limited to those aged ≥18 years and answering all pertinent questions (n=11 157). Outcomes: The primary outcome was a validated multicomponent measure of mental well-being (MWB). Additional outcomes included self-assessed life satisfaction (LS), life worth and trust in others. Results: Adult MWB, LS, life worth and trust were all significantly related to childhood violence and happiness. Relationships remained after controlling for sociodemographics. Thus, compared with those with happy, non-violent childhoods, respondents with unhappy, violent childhoods had adjusted ORs (95% CI, significance) of 3.10 (2.59 to 3.71, p<0.001) for low MWB, 3.62 (2.99 to 4.38, p<0.001) for low LS, 4.13 (3.40 to 5.01, p<0.001) for low life worth and 2.62 (2.20 to 3.11, p<0.001) for low trust. The impact of unhappy but non-violent childhoods were smaller but significant (p<0.001). The modelled impact of childhood factors predicted, for instance, that among unemployed white men aged 25–39 years from the most deprived communities, 27% of those with happy non-violent childhoods would have low MWB rising to 53% of those with unhappy violent childhoods. Conclusions: Adult well-being is strongly linked to childhood experiences. The addition of well-being measures to outcomes already associated with adverse childhoods (eg, adolescent antisocial behaviour and risks of adult disease) strengthens the case for investment in interventions to improve childhood experiences. Public health systems are well placed to ensure that policy to improve adult well-being exploits the potential for this to be realised through appropriate interventions.